Pengaruh Kemampuan Kerja Terhadap Kinerja Personel Satsamapta Polres Pamekasan Yang Dimediasi Oleh Pengembangan Karir - Woro Utari; Chamariah Chamariah; Dendi Apriliyanto Handika Putra (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Dendy Aprilianto Handika Pratama, 2025 . Influence Ability Work To Performance SATSAMAPTA personnel of the Police Pamekasan . Postgraduate Program of Wijaya Putra University, Surabaya. Based on its approach, this research is included in the type of explanatory research . The research sample was 80 respondents. The purpose of this research is 1) To test And analyze influence significant ability Work on performance SATSAMAPTA personnel of the Police Pamekasan . 2) For test And analyze influence significant ability Work towards development career SATSAMAPTA personnel of the Police Pamekasan . 3) For test And analyze influence significant development career on performance SATSAMAPTA personnel of the Police Pamekasan. 4) For test And analyze influence significant ability Work on performance SATSAMAPTA personnel of the Police Mediated Pamekasan​ by development career. The research results show that: 1) ability Work influential sword significant on performance SATSAMAPTA personnel of the Police The city of Pamekasan with mark original sample of 0.236. 2) ability Work influential positive significant towards development career SATSAMAPTA personnel of the Police The city of Pamekasan with mark original sample of 0.483. 3) development career influential positive significant on performance SATSAMAPTA personnel of the Police The city of Pamekasan with mark original sample of 0.432. 4) ability Work influential positive significant on performance SATSAMAPTA personnel of the Police Mediated Pamekasan​ by development career with mark original sample of 0.209.